Current Scenario of Fisheries and Aquaculture in India with Special Reference to Odisha: A Review on its Status, Issues and Prospects for Sustainable Development - Ngasotter, Soibam; Panda, Saumya Priyadarshini; Mohanty, Upasana; Akter, Sahina; Mukherjee, Susmita; Waikhom, David; Devi, Laishram Soniya (International Journal of Bio-resource and Stress Management, 2020)
Fisheries is an important sector in India, providing employment to millions of people and contributes to the food security of the country. Presently, India ranks second in aquaculture and third in fisheries production, contributing 1.07% to the national GDP and 5.30% to the agriculture GDP. Odisha, an eastern Indian state on the coast of Bay of Bengal is one of the major fish producing maritime states and currently ranks 4th in total fish production after Andhra Pradesh, West Bengal and Gujarat. Odisha has an abundance of fisheries resources, both inland and marine, and is home to the largest brackish water lagoon (Chilika lake) in Asia and the second largest coastal lagoon in the world. The state has 0.683 million ha of freshwater resources, 0.418 million ha of brackish water resources and 480 Kms. of coastline and continental shelf area of 24,000 Km2, which provides excellent scope for fisheries development. There has been a tremendous increase in fish production, from 0.386 million tonnes in 2010-11 to 0.758 million tonnes in 2018-19, with an export income generation around ` 31,000 million during 2017-18. Although the production has increased a lot in the last decade, there still seems to be an acute shortage in the supply of freshwater fish since the state continues to import freshwater fish from the neighbouring states. Understanding the various issues faced by farmers and improvising strategies to address them will contribute to augment production and productivity. This article highlights the present status of fisheries in Odisha, constraints and challenges faced by the farmers and fishers, and prospects and strategies for further improvement and development in the state.